Defining and Characterizing Archaeological Quartzite: Sedimentary and Metamorphic Processes in the Lithic Assemblages of El Habario and El Arteu (Cantabrian Mountains, Northern Spain). (22nd April 2018) - Prieto, A.; Yusta, I.; Arrizabalaga, A.
Abstract : Quartzite was the second most‐often used lithic raw material in Europe in the Palaeolithic. However, this rock has not been characterized fully from the geo‐archaeological point of view. This study characterizes, defines and determines types of quartzite in northern Spain through a methodology that integrates petrography, digital image processing and X‐ray fluorescence. As a methodological foundation for the characterization of the material, it aims to open the possibility of discovering mechanisms of mobility, selection and management of quartzite by prehistoric societies. The types determined, based on the petrogenesis of the material, enable a better understanding of the archaeological sites of El Arteu and El Habario in the context of northern Spain in the Middle Palaeolithic.